Women and Terrorism: A Sketch on the Phenomenon of Terrorism in the International Scene - Herdi Sahrasad; Dedy Tabrani; Muhammad Ridwan; Al Chaidar (SIASAT, 2020)
The involvement of women in terrorism is not a new phenomenon. But the increasing number of women joining the terrorism movement shows an increasing tendency as a new phenomenon. This is because they care deeply about inequality, suffering and injustice, and are disappointed with the government's inability to eradicate poverty. Unfortunately, these women have not found a more reasonable solution to channel their concerns. Their involvement in terrorism and transnational organizations such as ISIS that supports the idea of the Caliphate - and even to some extent with similar regional experiments in Southeast Asia- can make women feel that they are part of a global movement for change .Efforts are needed to de-radicalize women and the spread of moderate Islam (wasatiyah) as well as adequate socio-economic development to realize justice and prosperity in efforts to counteract and prevent women from engaging in acts of terror.